The Various Respond of Student Toward Peer-Tutoring Method in Bilingual Program - Khoirul Latifah (Academica: Journal of Multidisciplinary Studies, 2017)
This paper is aimed to examine the respond of students toward peer-tutoring method in a bilingual program that is held by Teacher and Training Faculty of IAIN Surakarta. This research using qualitative descriptive approach, that using interviews to collect the data. The data then analyzed through the literature review. The results show that the peer-tutoring method could improve the ability of the students. But, there is some problem with the peer-tutoring method such as the low awareness of students to learn English and also the bad structure of the material made the learning atmosphere unconducive. Thus, the tutor should maximize their creativity in order to succeed the bilingual program.Keywords:bilingual program, peer-tutoring method, student, respond